Cobb Douglas Production Function Analysis with Multiple Linier Regression Method on Rice Farming Business in East Java Province - Kristopo, Mailan Bangun; Purnomo, Didit (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
One of the staple foods of the people of Indonesia besides corn is rice. East Java Province is a potential rice-producing area because most of its territory is an agricultural area. This makes the province continue to increase rice production for the continuity of Indonesia's food self-sufficiency, especially in the East Java region itself. This study aims to determine the effect of harvest area, agricultural labor, and rainfall on rice production in East Java Province during the period 2001-2021. The analysis used is the Cobb-Douglas production function with multiple regression analysis using the Eviews. The results showed that the harvest area and agricultural labor had a positive effect on rice production. Meanwhile, rainfall has no effect on rice paddy production.